Effect of L/D Ratio on the Performance of Two-Lobe Pressure Dam Bearing: Micropolar Lubricated. (25th February 2015) - Sharma, Sanyam; Krishna, C. M.
Abstract : Two-lobe pressure dam bearings are commonly used in high speed rotating machineries. Their use is considered more stable than plain cylindrical bearings. Such bearings have a dam in the upper half whereas the lower half is provided with a relief track. Performance of two-lobe pressure dam bearings under micropolar fluid is evaluated. Finite element method is used to solve the modified Reynolds equation. Fluid film pressures are obtained by solving modified Reynolds equation. Thus pressure obtained is used to find performance characteristics of this bearing. The dynamic performance characteristics are studied at various L / D ratios. Three L / D ratios are considered 1.6, 2.0, and 2.4 for the analysis purpose. Results obtained are presented for various micropolar parameters. Results show that stability of two-lobe pressure dam bearings increases with decrease in aspect ratio (L / D ).